Subaltern Agency and Economic Resilience of Marginalized Community in Aceh - Muhammad Suhaili Sufyan; Muhammad Ansor; Mawardi Mawardi; Syawaluddin Ismail (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2022)
This article examines the gender practices of a marginal community based on economic resilience among traditional women parking attendants in Aceh, Indonesia. It specifically aims to challenge the framing of prior scholarship, which generally states that the daily gender practice of the marginal Muslim community does not provide ample room for a woman’s autonomy. The data was collected using semi-structural interviews and non-participatory observations of ten traditional women parking attendants in Langsa, Aceh. Using the concepts of agency, the article shows the way the women of a marginal community formulate and redefine gender relations in their socio-cultural sphere. Finally, the finding shows the ambivalences and the contribution of the gender practice within the marginal community in Aceh over the enrichment of gender equality discourse in Muslim societies.==========================================================================================================ABSTRAK - Agensi Subaltern dan Resiliensi Ekonomi Kaum Marginal di Aceh. Artikel ini membahas praktik gender komunitas marjinal berdasarkan resiliensi ekonomi perempuan petugas parkirt radisional di Aceh, Indonesia. Secara spesifik, studi ini bertujuan menantang pembingkaian kesarjanaan terdahulu yang mayoritas menyatakan praktik gender sehari-hari komunitas Muslim marjinal tidak memberi ruang memadai terhadap otonomi perempuan. Data dikumpulkan melalui wawancara semi terstruktur dan observasi non-partisipatoris terhadap sepuluh petugas parkir perempuan tradisional di Langsa, Aceh. Hasil analisis dengan konsep agensi, tulisan ini memperlihatkan cara dimana perempuan pada komunitas marjinal memformulasi dan meredefinisirelasi gender dalam ruang sosio-kulturalnya. Temuan kajian juga memperlihatkan ambivalensi dan kontribusi praktik gender dalam komunitas marjinal di Aceh terhadap pengayaan wacana kesetaraan gender dalam masyarakat Muslim.